Autumn bloom phenology and magnitude influence haddock recruitment on Georges Bank - Leaf, Robert T.; Friedland, Kevin D. (ICES Journal of Marine Science, 2014)
The haddock ( Melanogrammus aeglefinus ) stock on Georges Bank in the Northwest Atlantic is characterized by extremely large recruitment events relative to spawning-stock biomass. Recent work has indicated that the dynamics of the preceding autumn bloom may have explanatory power to describe these events. In this paper, we examine the hypothesis that autumn phytoplankton dynamics affect the recruitment of haddock, examine the temporal and spatial characteristics of the autumn phytoplankton bloom on Georges Bank, and correlate individual sex-specific condition measurements of haddock made in spring to recruitment patterns. Autumn bloom characteristics vary considerably across Georges Bank with earlier-occurring and larger-integral blooms occurring on the northern flank. On average, autumn blooms start on day 273 (29 September) and persist ∼50 days. There was a significant negative correlation detected between bloom start date and recruitment and a significant positive correlation of bloom integral and recruitment. The survivor ratio log e ( R /SSB) was positively and significantly correlated with individual condition of females in spring. The analysis of autumn bloom on Georges Bank provides a predictive index for recruitment strength of haddock and has utility for the assessment of this stock.